Medical students' and doctors' attitudes toward older patients and their care: what do we know and where do we go from here? - Samra, Rajvinder (2013)
This thesis explores doctors’ and medical students’ attitudes toward older patients in UK hospital settings. There have been regular and strong assertions in the grey literature and the news media that negative attitudes toward older patients may contribute to the inequality of healthcare service provision and treatment for older patients, compared to younger patients (those aged under 65 years), in UK hospital settings. However, much of the evidence does not investigate or explore these attitudes using a theoretical framework of attitudes outlined in the scientific research literature. This thesis comprises three studies. Firstly, a systematic search and review (Study 1) was undertaken in order to determine how attitudes toward older patients had been explored to date in the English-language, scientific research literature. Results demonstrated that previous studies had focused on attitude measurement rather than exploring the content of attitudes toward older patients. In fact, there was little evidence that previous research had ever explored these attitudes, despite the number of studies attempting to measure them. Furthermore, the review indicated the lack of research emanating from UK settings. In Study 2, attitudes toward older patients and their care were explored in twenty-five in-depth interviews with medical students and doctors in a UK NHS Hospital trust. Data were thematically analysed and findings indicated that attitudes toward older patients and their care could be conceptualised as: (1) attitudes toward older patients and their healthcare needs, and (2) attitudes toward providing care for older patients (e.g. the social and organisational barriers and facilitators). Within these two domains, the themes, subthemes and nodes, which represent attitude content with increasing levels of specificity, are presented. The findings from Study 2 mark one of the first attempts in this research area to explore and describe the content of attitudes in line with a theoretical framework of attitudes. The final study, Study 3, explored the devaluation and unpopularity of the specialty of geriatric medicine as a future career choice in a sample of junior doctors. Having identified, in Study 2, that geriatric medicine was not highly regarded in a range of doctors and medical students, Study 3 aimed to ascertain whether this was due to the organisational and working environment or due to older patient-related factors in a recently-qualified sample of doctors. The findings indicated that organisational and work-related factors serve to discourage junior doctors from pursuing geriatric medicine, rather than factors related to the older patients treated on geriatric wards.